Pregunta
upstudy study bank question image url

(71) \( \log x=1-\log (x-3) \)

Ask by Daniel Potter. in the United States
Feb 27,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( x = 5 \)

Solución

We start with the equation:   log x = 1 - log(x - 3) Step 1. Add log(x - 3) to both sides to combine logarithms:   log x + log(x - 3) = 1 Step 2. Use the product rule of logarithms:   log [x(x - 3)] = 1 Step 3. Rewrite the equation in exponential form. Assuming the logarithm is base 10, we have:   x(x - 3) = 10¹ = 10 Step 4. Expand and rearrange the equation:   x² - 3x - 10 = 0 Step 5. Factor the quadratic equation:   (x - 5)(x + 2) = 0 Step 6. Solve each factor:   x - 5 = 0 ⟹ x = 5   x + 2 = 0 ⟹ x = -2 Step 7. Check the domain of the logarithms:   For log x: x > 0   For log(x - 3): x - 3 > 0 ⟹ x > 3 Thus, x must be greater than 3. The solution x = -2 does not satisfy this. Final Answer: x = 5.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the equation \( \log x = 1 - \log (x-3) \), we can use the properties of logarithms. First, we can rewrite it as: \[ \log x + \log (x-3) = 1. \] Using the property that \( \log a + \log b = \log(ab) \), we have: \[ \log(x(x-3)) = 1. \] This implies: \[ x(x-3) = 10^1 = 10. \] Expanding the left-hand side gives us: \[ x^2 - 3x - 10 = 0. \] Now, we can solve this quadratic equation using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{3 \pm \sqrt{(-3)^2 - 4 \cdot 1 \cdot (-10)}}{2 \cdot 1} = \frac{3 \pm \sqrt{9 + 40}}{2} = \frac{3 \pm \sqrt{49}}{2}. \] This simplifies to: \[ x = \frac{3 \pm 7}{2}. \] Calculating the two possible values, we find: \[ x = \frac{10}{2} = 5 \quad \text{and} \quad x = \frac{-4}{2} = -2. \] However, since the logarithm is only defined for positive values, we discard \( x = -2 \). Therefore, the solution to the equation is: \[ \boxed{5}. \] It's always important to check that the solution we found satisfies the original logarithmic equations! For \( x = 5 \): \(\log(5) = 1 - \log(2)\) simplifies correctly, confirming that \( x = 5 \) is indeed valid.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad